California Democratic State Central Committee receipt - Charles Warren:::::: (1968)
This document is a receipt dated August 9, 1968, from the California Democratic State Central Committee acknowledging payment of $20 in dues by Jane Tolmach. The payment covers her membership dues for the years 1968 through 1970. It identifies her as a delegate from the 13th Congressional District and includes signatures from committee officials and Tolmach herself.